Creating a Board Game to Enhance Analytical Thinking Abilit of The World’s Landmarks for Grade 8 Students at Khon Kaen University Demonstration School - Husmin, Saksit (Ratchaphruek Journal, 2025)
The objectives of this research were: 1) To develop the “Where are you?” board game, focusing on important world landmarks in Social Studies subject for Grade 8 students, using Design Thinking as the framework for game development; and 2) To compare the result of the analytical thinking skills of Grade 8 students regarding world landmarks before and after using the board game. The sample consisted of 30 Mathayomsuksa 2/1 students, semester 2, academic year 2023. The data collection tools included the “Where are you?” board game, a board game quality assessment form, an analytical thinking test, and a focus group discussion. The statistics used in this research were mean, standard deviation, and t-test. The results indicated that: 1) the "Where are you?" board game was successfully developed as an educational innovation in line with the set objectives, receiving an overall quality rating of “the highest” from three experts (mean = 4.63), and 2) students’ analytical thinking skills regarding world landmarks significantly improved after using the board game, at the .05 level. Shows that after playing board games Players have analytical thinking. About important world landmarks higher than before playing board games.